Acoustic manipulation by brood-parasitic honeyguide - Blair, Cameron (Department of Biological Sciences, 2025)
Brood-parasitic birds lay their eggs in the nests of other species (‘hosts'), and their chicks encounter the challenge of acquiring sufficient food from host parents. Many parasitic chicks require more food than host chicks, and so need to elicit high rates of provisioning through their begging displays. Greater (Indicator indicator) and lesser (I. minor) honeyguides are closely related brood parasites that require more food than host chicks, whom they kill soon after hatching. Previous research demonstrated that both species receive the same amount of food as an entire brood of hosts (little bee-eaters Merops pusillus and black-collared barbets Lybius torquatus respectively), and that their begging calls influence provisioning by host parents. However, the acoustic mechanisms facilitating this phenomenon remained unknown. In this dissertation, I first test whether greater and lesser honeyguides mimic the begging calls of their respective hosts and quantify the accuracy of acoustic mimicry. I then test the hypothesis that honeyguides elicit increased provisioning from host parents by mimicking an entire brood of host chicks. I found that while both honeyguides mimic their host's nestlings, they do not specifically replicate the sound of a brood rather than a single chick. Finally, I test the hypothesis that non-linear vocal phenomena (NLP) in honeyguide begging calls could facilitate a supernormal stimulus particularly when the pitch and temporal structure of begging calls is constrained (such as by selection for mimicry). NLP are known to indicate high-arousal states in other ecological settings, inspiring the hypothesis that elevated NLP could function to increase provisioning to parasitic chicks beyond levels individual host nestlings would receive. I found that greater honeyguides tended towards higher perceived roughness (a form of NLP) than single bee-eater nestlings, but not significantly so. Lesser honeyguide begging calls tended towards higher amplitude modulation frequencies and perceived roughness than single barbet nestlings, but this too was not significant. Since both these features are associated with the amplitude envelope, I conducted a playback experiment at black-collared barbet nests in the field in Zambia to test whether the shape of the amplitude envelope of honeyguide begging calls increases host provisioning. This cautiously suggested it did not, at least at the levels manipulated here. Together, these results show that honeyguides mimic the pitch and temporal structure of their primary hosts' begging calls but do not mimic a brood to increase host provisioning, contrary to previous suggestions. The results are inconclusive as to whether NLP could be exploited by honeyguides to increase host provisioning. NLP should be further examined as a potential signalling mechanism that could be exploited by brood parasites to elevate the level of provisioning by host parents. More generally, the signalling function of NLP in bird begging calls, which had not been examined prior to this dissertation, deserves further investigation.